2014
DOI: 10.1063/1.4887348
|View full text |Cite
|
Sign up to set email alerts
|

Single and double resonance spectroscopy of methanol embedded in superfluid helium nanodroplets

Abstract: Methanol is one of the simplest molecules that undergo torsional oscillations, and so it has been extensively studied in the gas phase by various spectroscopic techniques. At 300 K, a large number of rotational, torsional, and vibrational energy levels is populated, and this makes for a rather complicated spectrum, which is still not fully understood. It is expected that in going from 300 K to 0.4 K (the temperature of helium nanodroplets) the population distribution of methanol will mainly collapse into two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 96 publications
(97 reference statements)
3
23
0
Order By: Relevance
“…If only this isomer is present in helium nanodroplets, then only a single OH stretching band is expected. The band assigned to NaCl(CH 3 OH) in the IR spectrum is red-shifted by ∼430 cm −1 from the OH stretching band of the methanol monomer in superfluid helium, 18 implying a very significant weakening of the O−H bond when methanol forms a complex with NaCl. This is consistent with the formation of an IHB between the OH and the chloride ion.…”
Section: The Journal Of Physical Chemistry a Articlementioning
confidence: 99%
See 1 more Smart Citation
“…If only this isomer is present in helium nanodroplets, then only a single OH stretching band is expected. The band assigned to NaCl(CH 3 OH) in the IR spectrum is red-shifted by ∼430 cm −1 from the OH stretching band of the methanol monomer in superfluid helium, 18 implying a very significant weakening of the O−H bond when methanol forms a complex with NaCl. This is consistent with the formation of an IHB between the OH and the chloride ion.…”
Section: The Journal Of Physical Chemistry a Articlementioning
confidence: 99%
“…This is a relatively narrow range, and the frequencies of these absorption bands are well to the red of the OH stretching band of the isolated methanol molecule. 18 This red shift is characteristic of the formation of IHBs, which weaken the OH bonds and thereby lower the OH stretching frequencies. This effect has been seen previously in IR spectra of the anionic Cl − (CH 3 OH) n complexes, which have been studied in the gas phase by Lisy and co-workers.…”
Section: The Journal Of Physical Chemistry a Articlementioning
confidence: 99%
“…To the best of our knowledge, no microwave, infrared or IR/UV double resonance spectra of this binary complex have been reported so far, whereas its components are very well investigated. 13,14 Also, OH-O and OH-p isomers of methanol complexing the anthracene analog of anisole have been identified long ago by UV hole burning spectroscopy 15 and in that work, the study of methanol-anisole was actually suggested. In the context of calibrating quantum-chemical methods for the description of polar vs. dispersive interactions of alcohols with ethers, 16 we found that the most reliable among the routinely applicable methods predict the two docking sites to be essentially isoenergetic for methanolanisole, with at best a slight preference below 1 kJ mol À1 for the oxygen binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the effective centrifugal constant D * as a function of B * in comparison with the experimental data listed in Ref. 4,5,18,30,32,34,38,41,48,49,51,52 . In agreement with the established experimental and theoretical result, D * measured in helium droplets is found to be 10 2 − 10 4 times larger than the corresponding gas-phase value.…”
Section: Effective Spectroscopic Constantsmentioning
confidence: 94%